DISTRIBUTION OF AIR AND MINERAL MIXTURE BY MEANS OF THE CHANNELS OF A BOOM APPLICATOR FOR FERTILIZERS APPLICATION - M. S. Kuleshov; V. A. Makarov; N. M. Marchenko (Сельскохозяйственные машины и технологии, 2015)
Numerous studies established that the average crop yield depends on the nature of distribution of fertilizer doses in the field. Unevenness of fertilizers diffusion of considerably worsens plants responsiveness, reduces technological and biological advantages of a yield, promotes accumulation of nitrates in crops, and also leads to environmental pollution. For distribution of mineral fertilizers centrifugal and rod units that adequately apply fertilizers but don’t guarantee the required quality of particle distribution on the field are most popular. However nonuniformity makes 25 and 10 percent respectively. In this regard the working out of technological processes and work tools for machines ensuring application of fertilizers adapted to the types of plants mineral nutrition and substantiation of means of control and management of technological processes are a significant scientific problem. The functions of the variation in the ejectors diameter in boom applicators for applying of additional and basic doses of solid mineral fertilizers were substantiated. As the result it was defined that the function of the ejectors diameter variation depends on the inner diameter of the rod, speed profile of the air and mineral mixture moving along the rod, the number of ejectors on the rod. Basic calculations were derived from the fact that for the normally system operate equality of air and mineral mixture stream entering and leaving the rod through the ejectors should be retained. The created pressure of the air and mineral mixture could be approximated by the Clapeyron - Mendeleev equation in isothermal movement and written in the Descartes’ system of Euler equations.